Nanocomposite Thin Film of Poly(3-aminobenzoic acid) and Multiwalled Carbon Nanotubes Fabricated through an Electrochemical Method - Paphawadee Netsuwan; Wirat Chaisu; Sukon Phanichphant; Saengrawee Sriwichai (Advances in Materials Science and Engineering)
The composite thin films of poly(3-aminobenzoic acid) (PABA) and multiwalled carbon nanotubes (MWNTs) are successfully fabricated through an electrochemical method. The composite mixtures containing 50 mM of 3-aminobenzoic acid with various concentrations of MWNTs (1.0, 2.5, 5.0, 7.5, and 10 mg/mL) in 0.5 M H2SO4 were prepared and used in this study. Cyclic voltammetry (CV) was used for fabrication and monitoring the electropolymerization of the composite thin films with potential range of 0 to 1100 mV for 5 cycles at scan rate of 20 mV/s on indium tin oxide- (ITO)-coated glass substrate. UV-vis absorption spectroscopy, atomic force microscopy (AFM), and scanning electron microscopy (SEM) techniques were employed to characterize the obtained composite thin films. It was found that MWNTs can enhance the peak current of CV traces of the PABA/MWNTs composite thin films without affecting the UV-vis absorption spectra. The surface morphology of the thin films can be studied using AFM and SEM techniques.